2009
DOI: 10.1021/jp8083327
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of the Ionic Liquid 1-Ethyl-3-methylimidazolium Tetrafluoroborate in Dichloromethane Using a Combined DFT-NMR Spectroscopic Approach

Abstract: DFT methods in combination with NMR spectroscopy are used to investigate possible variants of the molecular structure of the ion pairs of the ionic liquid (IL) 1-ethyl-3-methylimidazolium tetrafluoroborate, [EMIM][BF(4)], in dichloromethane. According to the computations of the chemical shifts, experimental NMR spectra can be rationalized by an equilibrium between ca. 70-80% of structures with the anion positioned near to the C2 atom of the imidazolium ring and ca. 20-30% of structures with the anion close to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 42 publications
(59 reference statements)
10
59
0
Order By: Relevance
“…Combined, these data indicate the ion pairing persists in the CD 3 CN solvent, at least to some extent, and the main contact is between the anion and the ring proton at the 2-position as expected. [30,31] In addition, the IR spectra of salts 2-7 show characteristic absorptions of the imidazolium ring. It has been reported that ionic liquids tend to form cation-anion aggregates and these aggregates have been investigated by ESIMS.…”
Section: Resultsmentioning
confidence: 99%
“…Combined, these data indicate the ion pairing persists in the CD 3 CN solvent, at least to some extent, and the main contact is between the anion and the ring proton at the 2-position as expected. [30,31] In addition, the IR spectra of salts 2-7 show characteristic absorptions of the imidazolium ring. It has been reported that ionic liquids tend to form cation-anion aggregates and these aggregates have been investigated by ESIMS.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29,73,80] As the imidazolium cation is surrounded by anions, the 1 H NMR shift of H 2 , H 4 and H 5 is a result of an equilibrium of several ion-pair structures. [81] Increased p stacking-as predicted for an increasing concentration of ILs diluted in common solvents-generally leads to a shift towards lower ppm values. [28] In our case of pure ILs it appears unlikely that the very large and weakly coordinating [Pf 2 …”
Section: A C H T U N G T R E N N U N G [Tf 2 N] In the Low-energy In-mentioning
confidence: 92%
“…Accordingt oE quations (1)-(6), the two interaction-energy parameters (g 21 4 -water mixtures are all shifted upfield upon dilution with water,w hereas those of OÀ Ha lways shift downfield, thus indicatingt hat the ILs dissociate gradually with increasing water contenta nd that the self-association interactions of water gradually replace the interactions between water andt he cations and anions,w hich is consistent with previousr eports. [12,19] According to the literature, [12,15,[40][41][42] ( Figure 1 (Figure 2). For the same system, the range of Dd for C2ÀHi ss lightly smaller than that for C4ÀHa nd C5ÀH; this indicates that the C2ÀH···Oi nteraction is stronger than the C4ÀH···O and C5ÀH···O interactions.…”
Section: Eyring-uniquac Viscosity Equationmentioning
confidence: 99%
“…[26][27][28] It is well-known that the ability of the C2ÀHp roton of the cation of [C n mim]BF 4 to form hydrogen bonds with protona cceptors, such as BF 4 À and water,i sm uch greater than that of C4ÀHa nd C5ÀH. [15] Therefore, the hydrogen-bonding interaction of C2ÀHo f[ C n mim]BF 4 is often used to represent the intermolecular interaction of the cation. [14,19] For example, in our previousw ork, [14] the local compositiono f1 -ethyl-3-methylimidazolium tetrafluoroborate ([Emim]BF 4 )i n[ Emim]BF 4 -water mixture has been calculated by using the interaction-energy parameter obtained from the 1 HNMR chemical shifts of C2ÀH and hasb een compared with the bulk composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation